ANALYSIS OF THE IMPACT OF CARBOHYDRATES ON HUMAN HEALTH AND DISEASE - Daulay, Rabiah Afifah; Iskandaria, Weyni; Sari, Sri Melina; Aminah, Siti; Tambunan, Sari Putri Ramadhani; Arya, Muhammad (Transpublika Publisher, 2022)
The aim of this research is to comprehensively investigate the pivotal role of carbohydrate nutrition in supplying energy to the human body and its implications for health. Over recent decades, the surge in diseases like obesity and type II diabetes, often linked to carbohydrate consumption, has raised concerns. Drawing upon an extensive review of literature, this qualitative study goes beyond surface-level analysis to delve deeply into the intricate relationship between carbohydrate intake, gut microorganisms, and their impact on human well-being. By adopting a qualitative approach, this research aims to provide a nuanced understanding of the multifaceted effects of carbohydrates, particularly emphasizing their influence on the growth and equilibrium of gut microorganisms. The symbiotic relationship between carbohydrates and gut microbiota extends its reach to mental health and various organic systems. However, disruptions in this balance may yield adverse consequences, warranting a comprehensive exploration. The study uncovers a spectrum of diseases associated with carbohydrate-related factors, encompassing cardiovascular ailments, cancer, chronic kidney failure, and asthma. Additionally, the research highlights the negative influence of simple and refined carbohydrates on mood-related aspects such as alertness and fatigue. This research seeks to elucidate the complex interplay between carbohydrate nutrition, gut microbiota, and human health. By achieving this objective, the study contributes valuable insights that can guide healthcare professionals, policymakers, and individuals toward informed dietary choices and improved overall well-being.